2022
DOI: 10.1186/s13027-022-00453-z
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of oncogenic HPV and HPV-related dysplasia five years after a negative HPV test by self-sampling in elderly women

Abstract: Purpose Cervical cancer prevention for older women can be challenging since there are no specific guidelines for this group. This study aimed to determine the incidence of oncogenic HPV and HPV-related dysplasia in elderly women 5 years after being HPV negative. Methods Invited women participated five years earlier in a study where self-sampling for HPV testing was applied, at this time, they were all HPV negative. The women were now, five years la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…A recent Swedish study offering a self-sampling HPV Test to women aged 65 and older also showed a very low rate of persistent hr HPV infections with only 1.3%. In the same study, it was also shown that women with a newly acquired hr HPV infection had a higher risk for LSIL, compared to women with a persistent HPV infection of longer duration [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent Swedish study offering a self-sampling HPV Test to women aged 65 and older also showed a very low rate of persistent hr HPV infections with only 1.3%. In the same study, it was also shown that women with a newly acquired hr HPV infection had a higher risk for LSIL, compared to women with a persistent HPV infection of longer duration [ 18 ].…”
Section: Discussionmentioning
confidence: 99%